2022
DOI: 10.3389/fneur.2022.900520
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Responses in Post-Stroke Hemiplegic Patients Modulated by Acupuncture at Yanglingquan (GB34): A fMRI Study Using Intersubject Functional Correlation (ISFC) Analysis

Abstract: Motor dysfunction is common in patients with stroke. Acupuncture has become an acceptable alternative method for stroke rehabilitation. Previous studies have shown various functional connectivity changes activated by acupuncture. We introduced intersubject correlation (ISC) and intersubject functional correlation (ISFC) analyses into the functional magnetic resonance imaging (fMRI) for ischemic stroke to seek a common activation and suppression pattern triggered by acupuncture. In this study, 63 ischemic strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Chen et al further revealed a cortico-subcortical connectivity between the cerebellum and the sensory motor network (SMN) (Chen et al, 2022). Acupuncture can regulate the SMN to relieve hemiplegia, numbness and other symptoms (Wang et al, 2022;Peng et al, 2023). Thus, we consider that 3-min acupuncture stimulation may improve motor dysfunction in stroke patients more effectively by regulating the SMN including the cerebellum compared with shorter stimulation.…”
Section: Discussionmentioning
confidence: 90%
“…Chen et al further revealed a cortico-subcortical connectivity between the cerebellum and the sensory motor network (SMN) (Chen et al, 2022). Acupuncture can regulate the SMN to relieve hemiplegia, numbness and other symptoms (Wang et al, 2022;Peng et al, 2023). Thus, we consider that 3-min acupuncture stimulation may improve motor dysfunction in stroke patients more effectively by regulating the SMN including the cerebellum compared with shorter stimulation.…”
Section: Discussionmentioning
confidence: 90%
“…Acupuncture, an important facet of traditional Chinese medicine, has demonstrated clinical efficacy in many conditions, including pain, mood disorders, and stroke, by modulating neural responses in the brain (51)(52)(53). Brain activation leads to enhanced blood flow, blood volume, and oxygen saturation in the cerebrum, thereby increasing deoxyhemoglobin levels, which is proportional to the magnetic resonance signal on functional MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Yanglingquan (GB34), also known as “confluential point of sinews,” has the effect of relaxing and strengthening sinews, thus it is considered as a classic acupoint for relieving spasticity. A fMRI study illustrated that acupuncture at GB34 may improve the motor function recovery in post-stroke hemiplegic patients via affecting the functional connectivity of the brain ( 56 ). It was found that the anti-spastic action of acupuncture at GB34 for post-stroke spasticity was related to its alleviation of spinal hyperreflexia via KCC2-mediated spinal GABA A activation ( 57 ).…”
Section: Discussionmentioning
confidence: 99%